2021
DOI: 10.1038/s41467-021-23990-4
|View full text |Cite
|
Sign up to set email alerts
|

Access to enantioenriched compounds bearing challenging tetrasubstituted stereocenters via kinetic resolution of auxiliary adjacent alcohols

Abstract: Contemporary asymmetric catalysis faces huge challenges when prochiral substrates bear electronically and sterically unbiased substituents and when substrates show low reactivities. One of the inherent limitations of chiral catalysts and ligands is their incapability in recognizing prochiral substrates bearing similar groups. This has rendered many enantiopure substances bearing several similar substituents inaccessible. Here we report the rationale, scope, and applications of the strategy of kinetic resolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…To avoid the innate low reactivity of direct reactions on sterically congested tertiary alcohols, Fang, Xu, and coworkers reported, in 2021, an efficient and indirect protocol to synthesize enantioenriched tertiary alcohols via the strategy of kinetic resolution of auxiliary adjacent alcohols (KRA*) that is based on an isothiourea-catalyzed acylative KR of racemic diastereoenriched tertiary diols 55 (Scheme 11a). 33 In this study, the isothiourea-catalyzed KR process showed excellent reactivity and high resolution efficiency for a wide variety of diols bearing diaryl or dialkyl tertiary alcohols, providing s values ranging from 24 to 500. Notably, tertiary alcohols with three alkyl substituents were found to be compatible substrates, which represent one of the most challenging substrates due to the similar steric and/or electronic properties.…”
Section: Short Review Synthesismentioning
confidence: 77%
“…To avoid the innate low reactivity of direct reactions on sterically congested tertiary alcohols, Fang, Xu, and coworkers reported, in 2021, an efficient and indirect protocol to synthesize enantioenriched tertiary alcohols via the strategy of kinetic resolution of auxiliary adjacent alcohols (KRA*) that is based on an isothiourea-catalyzed acylative KR of racemic diastereoenriched tertiary diols 55 (Scheme 11a). 33 In this study, the isothiourea-catalyzed KR process showed excellent reactivity and high resolution efficiency for a wide variety of diols bearing diaryl or dialkyl tertiary alcohols, providing s values ranging from 24 to 500. Notably, tertiary alcohols with three alkyl substituents were found to be compatible substrates, which represent one of the most challenging substrates due to the similar steric and/or electronic properties.…”
Section: Short Review Synthesismentioning
confidence: 77%
“…In contrast to the catalytic KR of racemic secondary alcohols, 4 reliable methods for the non-enzymatic KR of tertiary alcohols remain few. 5–9 Several groups have reported the use of chiral Lewis base (nucleophilic) catalysts 6 and chiral transition metal catalysts. 7 In the methodologies reported for the KR of racemic tertiary alcohols in recent years, chiral phosphoric acids (CPAs), which are one of the most powerful and privileged organocatalysts employed in a broad range of enantioselective transformations, 10 have proven to be excellent catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Despite all of these challenges, some elegant and efficient strategies for the KR of tertiary alcohols have been reported in the literature in the presence of transition metal catalysts or organocatalysts. Most of those methods are modifications of the hydroxyl group with the electrophilic intermediate activated by a chiral catalyst (Scheme b). For example, Miller and co-workers , developed an efficient kinetic resolution method for tertiary alcohols via enantioselective O-acylation by using a peptide catalyst bearing a nucleophilic imidazole (Scheme a).…”
mentioning
confidence: 99%